Herder on nationality, humanity, and history - Barnard, F. M. (Frederick M.) (McGill-Queen's studies in the history of ideas ;, 2003)
"The core of J.G. Herder's philosophy of nationalism lies in the conviction that human creativity must be embedded in the culture of a particular communal language. While he acknowledged that this cultural particular must be integrated into a more universal humanity, he insisted that each culture should preserve its incommensurable distinctiveness. He also called for a new method of enquiry regarding history, one that demands empathetic sensitivity toward the uniquely individual while realizing that there are few gains without losses. F.M. Barnard shows that Herder anticipated modern theories of the dynamics of cultures and traditions through the problematic interplay of persistence and change and that his speculations on cultural and political pluralism, on language as a democratic bond, and on the possible fusion of communitarian and liberal dimensions of public life remain relevant to contemporary debates."--Jacket